Dynamic changes of Sonic Hedgehog signaling pathway in gastric mucosa of rats with MNNG‐induced gastric precancerous lesions. Issue 7 (7th December 2018) - Cai, Danli; Yu, Jianshun; Qiu, Jing; He, Beihui; Chen, Zhiyun; Yan, Maoxiang; Liu, Qingsheng
Abstract: Objective: To explore the changes of Sonic Hedgehog (Shh) signaling pathway in the stomach mucosa during the formation of gastric precancerous lesions. Methods: A total of 72 suckling rats in half genders were randomly and equally divided into the normal group and model group. The rats in the model group were administered with 0.1 ml 1‐methyl‐3‐nitro‐1‐nitrosoguanidine (MNNG) at the dosage of 800 mg/L for 10 days, whereas the rats in the normal group were similarly administered with normal saline. A total of 12 rats in each group were killed at the end of 10th, 22nd, and 34th weeks in half gender, respectively. Histopathological changes of the gastric mucosa were observed by hematoxylin and eosin (HE) staining; the levels of Shh, Ptch1, Smo, Gli1, Gli2, Gli3, SuFu, Cyclin D1, Cyclin E1, c‐Myc, and β‐actin mRNAs in the gastric mucosa were determined by real‐time polymerase chain reaction; while the protein expression of Shh, Ptch1, Smo, Gli1, SuFu, Cyclin D1, Cyclin E1, c‐Myc, and p‐c‐Myc was detected by western blot analysis. Results: With the development of atrophy and dysplasia of gastric mucosa, the levels of Shh, Smo, Gli1, Cyclin D1, Cyclin E1, and c‐Myc mRNAs increased, while those of Ptch1 and SuFu decreased. The expression of Shh, Smo, Gli1, Cyclin D1, Cyclin E1, and p‐c‐Myc proteins were elevated, while the expression of Ptch1 and SuFu proteins were decreased, however, without statistical difference. Conclusions: Shh signaling is activated during the formation of gastric precancerous lesions, which indicates that the Shh signaling pathway participates in the development and progression of gastric precancerous lesions. Abstract : Sonic Hedgehog (Shh) signaling is activated during the formation of gastric precancerous lesions, which indicates that the Shh signaling pathway participates in the development and progression of gastric precancerous lesions.